PF.50 Termination of Pregnancy For Fetal Anomaly – Are We Providing a Woman Centred Service?. (26th April 2013) - Fisher, J; Robson, SC; Lohr, PA; Lafarge, C
Abstract : Background: With improved antenatal testing, more women face the possibility of termination of pregnancy for fetal anomaly (TOPFA). Choice of medical or surgical TOPFA method is advocated by the RCOG based on similar risk profiles 1 . We investigated women's experiences of TOPFA by surveying members of Antenatal Results and Choices (ARC) - a national charity supporting parents throughout antenatal testing. Methods: A link to an online questionnaire with structured and open-ended questions was emailed to 600 members and publicised on the ARC website. The survey was open from 20/1/12 – 7/3/12. Responses were downloaded, cleaned, coded, and analysed using SPSS and Microsoft Excel. TOPFAs after 24 weeks gestation and selective reductions were excluded. Results: 351 responses were analysed. Indications for termination were categorised as chromosomal/genetic (56%), structural (42%), and other (2%). Mean gestation at TOPFA was 17 weeks. Overall, 74% were only offered medical TOPFA; 14% were offered a choice. At ≤15 weeks gestation, 31% were offered choice vs. 5% at 16–24 weeks (p < 0.001). 16% with a chromosomal/genetic indication were offered choice vs. 12% with a structural/other indication (p = 0.25). Overall, 78% underwent medical TOPFA; 88% indicating it was the only method offered. Of those offered choice, 60% chose surgical. Women who had surgical TOP were more likely to feel it was right for them. Conclusion: Accepting the limited survey sample, our survey suggests women are not offered a choice of method for TOPFA, impacting on satisfaction. Service delivery needs improvement to meet national guidance and women's needs. Reference: Termination of Pregnancy for Fetal abnormality in England, Scotland and Wales Report of a Working Party (May 2010) RCOG.